The Existence of the Development of Integrated Islamic Education Institutions (SDIT) and Madrasah in Purwodadi Village - Wina Calista; Mudiyono Mudiyono (Al Hikmah: Journal of Education, 2021)
This research aims to analyze the problem of the development of integrated Islamic elementary schools and madrasah in purwodadi village. The approach used is a descriptive approach to analysis of qualitative data. In addition, the data collection techniques used in the study used observation, interviews and documentation. The result of this study is the problem of the development of Islamic-based school trends (SDIT) that have an impact on madrasah. Purwodadi Village has 1 General Kindergarten and 2 TKIT, elementary school consists of 2 State Elementary Schools and 2 SDIT and Madrasah Ibtida'iyah (MI) only 1. So that the total elementary school age education institution in one village has 4 elementary schools. The development of an Integrated Islamic school in purwodadi village had an impact on madrasah. One of the advantages of SDIT has learning programs such as memorization of quran and hadith, sunnah Dhuha prayer before starting learning activities, murojaah, dzuhur prayer before school, Friday almsgiving, and other activities. These activities are then a special consideration for parents in choosing educational institutions for their children. While madrasah does not have an activity program that supports learning such as in SDIT. One of the effects is the reduced interest of students who attend madrassas. This is because of the trend of Islamic schools that develop in the village with a variety of learning programs offered.